CONCEPT, TYPES AND CONSEQUENCES OF LANGUAGE CONTACTS: NEW APPROACHES - Korbozerova, Nina; Obruchnikova, Olena (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2024)
The article studies a series of problems connected with the definition of linguistic contacts, such as the complicated sociolinguistic, linguocognitive and ethnic-cultural phenomenon. Such contact is accompanied by the specific processes of linguistic interferences, linguistic code change and linguistic borrowings. Linguistic contacts are due to non-linguistic phenomena such as population migration, the coexistence of different ethnic groups in the same territory or in the surrounding area, wars, colonization, political, economic, cultural and educational connections. Language contacts are closely linked with types of interethnic cultural contacts. There are several types of linguistic contacts: contacts according to their duration and stability; according to direct and indirect connections; contacts between related and unrelated languages; contacts with unilateral and with mutual influence; marginal and intraregional contacts; casual and permanent contacts; natural and artificial contacts. The consequences of language contacts. Language contacts are based on linguistic and sociolinguistic phenomena. Due to its significant nature, three aspects of language contact are distinguished: the consequences of language contact that affect the language; the consequences that concern the speaker of a language and the consequences that have effects on communication. Due to their duration, the consequences of linguistic contacts can be short-term and long-term. As a result of linguistic contacts can be formed pidgins and creole languages, which are the adstratum phenomena, or one of the contacted languages can be assimilated with the won/winning language, which are the substratum or superstratum phenomena. The different linguistic levels of linguistic contacts have a very stable character: the most stable is the lexical level, the least stable are the phonology and morphology levels.____________References:• Familia indoeuropea, http://www.proel.org/index.php?pagina=mundo/indoeuro• https://lenguayliteraturasuperior.wordpress.com/2010/01/20/las-lenguas-del-mundo-y-de-europa/• Verba,  Curso de lexicología comparada (español-ucraniano). Vinnytsia: Nova Knyha, 2021. 232 p.• https://es.wikipedia.org/wiki/Lenguas_romances• https://www.inesem.es/revistadigital/idiomas/lenguas-indoeuropeas/
Keywords: linguistic contacts, linguistic interferences, the exchange of linguistic codes, types of borrowings, the dominant language, indigenous languages, language variability.